Application of root cause analysis in improvement of product quality and productivity - Dalgobind Mahto; Anjani Kumar (Journal of Industrial Engineering and Management (JIEM), 2008)
Root-cause identification for quality and productivity related problems are key issues for manufacturing processes. It has been a very challenging engineering problem particularly in a multistage manufacturing, where maximum number of processes and activities are performed. However, it may also be implemented with ease in each and every individual set up and activities in any manufacturing process. In this paper, root-cause identification methodology has been adopted to eliminate the dimensional defects in cutting operation in CNC oxy flame cutting machine and a rejection has been reduced from 11.87% to 1.92% on an average. A detailed experimental study has illustrated the effectiveness of the proposed methodology.
Keywords: 650; root cause analysis; cause and effect diagram; interrelationship diagram andcurrent reality tree